Pengaruh Kontribusi Pajak Daerah, Pendapatan Asli Daerah dan Restribusi Daerah terhadap Belanja Daerah (Suatu Kajian Studi Literatur Manajemen Keuangan Daerah) - A. Manafe, Henny; Perseveranda, M.E.; Rosaline Koli, Feby (Dinasti Review Publisher, 2023)
The writing of this scientific paper refers to other works, especially research that examines the influence of each variable or other factor that has an impact on regional spending, namely the contribution of local taxes, regional original income, and regional fees. affect the variable so that it can be used for further writing. The results obtained consist of: 1) Regional regional tax contributions have a positive or crucial impact on regional spending; 2) Local own-source revenue has a positive or crucial impact on regional spending; 3) Regional fees have a positive or crucial impact on regional spending; 4) The contribution of regional taxes, regional original revenues, and regional fees have a simultaneous positive and significant impact on regional spending.